The Role Of Islamic Religious Education In Preventing Drug Abuse Among Adolescents (Case Study Of Adolescents In Asam Jawa Village, Aekbatu) - Yosi, Nelfa; Pasaribu, Munawir; Pohan, Selamat (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to analyze the role of Islamic religious education in preventing drug abuse among adolescents in Asam Jawa-Aekbatu Village, to analyze how the efforts made by the government, community leaders, and parents in preventing drug abuse among adolescents in Asam Jawa-Aekbatu Village, to analyze what supporting and inhibiting factors the role of Islamic religious education in preventing drug abuse among adolescents in Asam Jawa-Aekbatu Village. The study used a qualitative approach with case studies, involving interviews and observations. While the type of research used was field research. Based on the results of the analysis in Asam Jawa-Aekbatu Village, it shows that Islamic Religious Education has an influence as an effort to prevent drug abuse by instilling moral and ethical values, which are carried out by the community and adolescents of Asam Jawa-Aekbatu Village, they carry out positive activities such as holding routine religious studies, other religious activities, environmental mutual cooperation and counseling on the prevention of drug abuse held by the government of Asam Jawa-Aekbatu Village.